Emerging technologies revolutionise insect ecology and monitoring. (October 2022) - van Klink, Roel; August, Tom; Bas, Yves; Bodesheim, Paul; Bonn, Aletta; Fossøy, Frode; Høye, Toke T.; Jongejans, Eelke; Menz, Myles H.M.; Miraldo, Andreia; Roslin, Tomas; Roy, Helen E.; et al.
Abstract : Insects are the most diverse group of animals on Earth, but their small size and high diversity have always made them challenging to study. Recent technological advances have the potential to revolutionise insect ecology and monitoring. We describe the state of the art of four technologies (computer vision, acoustic monitoring, radar, and molecular methods), and assess their advantages, current limitations, and future potential. We discuss how these technologies can adhere to modern standards of data curation and transparency, their implications for citizen science, and their potential for integration among different monitoring programmes and technologies. We argue that they provide unprecedented possibilities for insect ecology and monitoring, but it will be important to foster international standards via collaboration. Highlights: Technological developments are opening new possibilities for biodiversity monitoring, but – especially for insects – they come with their own unique set of limitations. Due to the vast diversity of insects, of which at least 80% remain undescribed, traditional monitoring is unable to provide even basic knowledge of the state of most insect species in most places. We appraise four emerging tools and technologies (computer vision, acoustic monitoring, radar, and molecular methods) that provide unprecedented opportunities for insect ecology. These technologies can enhance spatial, temporal, and taxonomic coverage of monitoring, but none can monitor all insects at all scales, and each comes with a set of limitations. Technological integration, open data, and international standards are needed to harness the full potential of novel technologies for insect monitoring.